Digital transformation in business: challenges and opportunities for management in the modern era - Siregar, Ilhamsyah; Firmansyah, Edy (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2024)
Digital transformation has become a crucial element in the modern business world, bringing significant changes to company operations, management strategies, and business models. While digitalization offers various opportunities, such as increased efficiency, product innovation, and new technology-based business models, challenges in its implementation remain obstacles for many organizations. One of the main challenges is the digital skills gap among employees, which can hinder technology adoption and reduce productivity. Additionally, organizations often struggle to measure the return on investment (ROI), making strategic planning and data-driven analysis essential to ensuring the success of digital transformation. On the other hand, the development of digital business models, such as the sharing economy, subscription-based services, and AI-driven automation, presents significant opportunities for companies to enhance competitiveness and expand their market reach. Therefore, businesses must adopt a comprehensive approach to digital transformation, including workforce capacity building, well-planned technology investments, and innovation in business strategies. This study aims to analyze the challenges and opportunities of digital transformation in business and provide recommendations for management in navigating the digital era. With the right strategies, organizations can maximize the benefits of digitalization and create sustainable competitive advantages in an increasingly dynamic market.